In vitro cytotoxic activity of Cymbopogon citratus L. and Cymbopogon nardus L. essential oils from Togo - Koffi Koba; Komla Sanda; Catherine Guyon; Christine Raynaud; Jean-Pierre Chaumont; Laurence Nicod (Bangladesh Pharmacological Society, 2008)
The leaf essential oils of Cymbopogon citratus L. and Cymbopogon nardus L. (Poaceae) from Togo were steam-distilled, analyzed for percentage composition and investigated in vitro for their potential cytotoxic activity on human epidermic cell line HaCat. The percentage composition showed that the main constituents of essential oils samples were respectively geranial (45.2%), neral (32.4%) and myrc¨ne (10.2%) for C. citratus essential oil and citronellal (35.5%), geraniol (27.9%) and citronellol (10.7%) for that of C. nardus. The in vitro cytotoxicity bioassays on human epidermic cell line HaCaT revealed that the toxicity of the essential oil from C.citratus (IC50: 150 µL.mL-1) was higher than that of the essential oil from C.nardus (IC50: 450 µL.mL-1). Pure commercial neral, geranial, and citronellal standards showed respectively the following IC50 values: 100, 250 and 300 µL.mL-1). Conversely, pure citronellol standard appeared almost non-toxic (IC50>1000 µL.mL-1), proving the major role played in synergy by neral and geranial in the overall toxicity showed by the citratus oil sample tested in this work.